From Suffering to Hope. The Survey of Rubble as a Measure of Resilience (diségno, 2020)
As in the Japanese art of kintsugi, where fragments of broken ceramics are recomposed using the gold dust insert, in the installation Canapa Nera, presented by the Regione Umbria at Milan Design Week 2018, the preciousness of the material was substantiated by an alchemical mix of the hopes that vibrate in the fibres of the black hemp of the Valnerina with the memories that permeate the rubble of the diruti walls of Norcia following the seismic events that in 2016 upset Central Italy. Canapa Nera was a long two-faced wall, characterised on one side by a polyptych of eleven large canvases of hemp inspired by the plots and colours of the annual flowering of the Pian Grande and on the other side by a chaoticexplosion of variegated rubble, the recovery of which entailed both operational and interpretative difficulties, because they were linked both to the extraction and to the identification of the most suitable survey techniques. As part of the study undertaken, the measurement and graphic restitution of the individual rubble was aimed at enhancing its identity value, celebrated through the recomposition of a fragmented whole, scattered among voids. Making measurable the poetic space that marks the gap between suffering and hope.
Keywords: earthquake; resilience; identity; rubble; measure